2023
DOI: 10.1002/adfm.202215021
|View full text |Cite
|
Sign up to set email alerts
|

Relay Catalysis of Multi‐Sites Promotes Oxygen Reduction Reaction

Abstract: The two‐electron pathway to form hydrogen peroxide (H2O2) is undesirable for the oxygen reduction reaction (ORR) in iron and nitrogen doped carbon (Fe–N–C) material as it not only lowers the catalytic efficiency but also impairs the catalyst durability. In this study, a relay catalysis pathway is designed to minimize the two‐electron selectivity of Fe–N–C catalyst. Such a design is achieved by introducing two other sites, that is, MnN4 site and α‐Fe(110) face. A combination of transmission electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Efficient strategies for preventing the demetalation of SACSs have been reported sparingly. , Recent studies have shown that interaction with metallic particles such as clusters and nanoparticles can inhibit the demetalation of SACs, making it one of the few strategies that offer promise for inhibiting demetalation. , However, the mechanisms that underlie the stabilization of SACs by metallic particles remain poorly understood. The specific property or properties of SACSs that are altered following the introduction of particles and how such modifications prevent demetalation are yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient strategies for preventing the demetalation of SACSs have been reported sparingly. , Recent studies have shown that interaction with metallic particles such as clusters and nanoparticles can inhibit the demetalation of SACs, making it one of the few strategies that offer promise for inhibiting demetalation. , However, the mechanisms that underlie the stabilization of SACs by metallic particles remain poorly understood. The specific property or properties of SACSs that are altered following the introduction of particles and how such modifications prevent demetalation are yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Figure a, H 2 O 2 released from Co–N 4 can migrate to MnCo 2 O 4 and be further reduced to H 2 O. In this way, a 2e – + 2e – relay pathway is realized through the interaction of two different types of catalytic sites. ,, This calculation is conventionally based on sufficiently separated active sites. However, synergy between adjacent active sites remains an open question.…”
Section: Resultsmentioning
confidence: 99%
“…Many electrochemical reactions, such as the oxygen reduction reaction (ORR), nitrogen reduction reaction (NRR), carbon dioxide reduction reaction (CO 2 RR), etc., involve multielectrons and intermediates, thus imposing high requirements on electrocatalysts. To smoothly complete the entire chemical reaction, the catalysts need to properly adsorb all intermediates. Since it is difficult for a single type of active site to have moderate adsorption/desorption strengths to all intermediates, relay catalysis has been developed as a solution. Relay catalysis is essentially a kind of synergistic catalysis. The intermediate species formed on one type of active site migrate to another active site on the same catalyst to complete the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…After 15 000 CV cycles, Mn 1 @Fe-N-C/CNTs exhibit a slight decay of E 1/2 of 14 mV, which is much smaller than Fe-N-C/CNTs (26 mV) (Figure S20 in the Supporting Information). It has been reported that the radicals attack on the Fe-N x sites is an important reason for ORR activity attenuation when a Fe-N-C catalyst is used . Therefore, we design a radical scavenging experiment to ascertain the scavenging ability of the radical for the catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the radicals attack on the Fe-N x sites is an important reason for ORR activity attenuation when a Fe-N-C catalyst is used. 50 Therefore, we design a radical scavenging experiment to ascertain the scavenging ability of the radical for the catalysts. According to recent reports, 26 the 2,2-azinobis(3-rthylbenzoline-6-sulfonate) (ABTS) was chosen as the probe molecule and Youke UV-vis spectroscopy was used to monitor the change of radical concentrations with ABTS.…”
Section: Resultsmentioning
confidence: 99%